The long-term effects of removal of sensorimotor cortex in infant and adult rhesus monkeys. - Passingham, R; Perry, V; Wilkinson, F (1983)
A comparison is made between the long-term effects of the unilateral removal of sensorimotor cortex in infant and adult rhesus monkeys. Both infants and adults recovered to a remarkable extent. They walked, climbed and jumped with ease. However, neither infant nor adult monkeys could grip food by using thumb and forefinger independently of the other fingers. It was demonstrated in the adults that there was a permanent impairment in the use not only of the fingers but also the wrist and forearm. The results do not support the claim made by Kennard (1942) that infants recover more completely than adults from the effects of brain lesions. An analysis of the relevant evidence suggests that compensation occurs only when the animal is very immature at the time of operation. The brain is much more mature in a neonatal monkey than a rat or hamster. True compensation can probably only occur in monkeys if the lesion is made well before birth.